Role of Clinical Laboratory in Diagnosis and Management of Di-abe¬tes Mellitus- Review Article - Farideh RAZI; Ensieh NASLI ESFAHANI; Bagher LARIJANI; Parvin PASALAR (Tehran University of Medical Sciences, 2015)
The aim of the clinical laboratory in endocrine disease diagnosis and management is detecting either the hormones or their downstream reaction metabolites or some other related substances. In the case of hormone measurement almost all the routine methods are based on immunoassay with different labels (radioimmunoassay, enzyme linked immunosorbant assay, chemiluminescence assays ...) and different sensitivity and specificity. But their related metabolites can be measured with different methods from simple biochemical to highly sophisticated methods. These tests are used either for diagnosis or monitoring. With respect to diabetes the tests are categorized to biochemical, immunological and genetic. In this paper we will describe the most common tests, but the genetic tests that are not used in routine investigations are out of the scope of this paper.   Keywords: Laboratory, Diagnosis, Diabetes